The contribution of Muslim scholars to the field of medicine (with particular reference to ibn Sina and al- Razi during the Islamic golden age) - Ashimi, Tijani Ahmad (2018)
Science is a part of the systematic knowledge of nature which is undoubtedly acquired through a methodology based on observation, hypothesis and experiment. In the Qur’an science is an essential activity for any Islamic community for it increases the understanding of the signs of God and hence brings the ummah closer to the Creator. Based on this fact, the scientific spirit of Muslim scientists and scholars flows from their consciousness of Tawhid (Unity of God), this tawhidic worldview has played a very vital role in exploring the physical world and discovers its secret (sunnatullah). Hence the famous Muslim scientists like alRazi, Ibn Sina, al- Biruni, Ibn al- Haitham, al Zahrawi just to mention a few, were all noted for their observational power and experimental tendencies as displayed in their wide ranging studies of the natural sciences. As such, these great scholars have produced a lot of books which then being the important references to the later researchers notably the westerners toward the end of the dark age of Europe. Thus, this humble paper by applying a historical approach aims to explore the biographies and the immense contributions vis-a- vis the two gigantic Muslim Scholars(Ibn Sina and al Razi) to the field of Natural sciences, with particular reference to their unique contributions in the aspect of medicine. Finally, the paper will provide a brief conclusion followed by some suggestions and recommendations.